Fundamentals of yarn winding - Koranne, Milind (Woodhead Publishing India in textiles., 2013)
Fundamentals of yarn winding explains principles related to yarn winding relevant even to the latest generation of winding systems. The book discusses various parameters related to build up of winding packages, their influence on package performance and optimisation according to end-user yarn tensioning and clearing devices, yarn splicers and various methods of package driving and yarn traversing. Basics of building winding packages are described in a simplified manner supported by numerous diagrams and photographs. Various terms associated with winding systems/packages are conceptually clarified like random winding, patterning, precision winding, gain, open wind, close wind, step precision winding etc. Principles of various winding systems along with basic mathematics involved are described. Current developments in winding machines have opened up immense possibilities in package building that demands through understanding of fundamental aspects on the part of the user. The book is useful to textiles students as well as textile professionals working in staple and synthetic yarn spinning, weaving, knitting, yarn dying, texturizing, sewing thread manufacturing, technical textiles etc. The book is also useful to professionals from other disciplines like chemical, electronics, computer and mechanical dealing with winding systems.